ASSESSING THE TRAINING OF HEU’ STUDENTS IN THE FIELD OF VOCATIONAL EDUCATION THROUGH PEDAGOGICAL STRATEGY: ON THE EXAMPLE OF UZBEKISTAN - Pozilova Shakhnoza Khaydaraliyevnal (Journals Park Publishing, 2022)
This article aims to develop a pedagogical strategy for preparing students for vocational education. The author presents the structure, components and conditions of preparation of students of higher education institutions for professional and pedagogical activity on the basis of a competency approach. The experimental sites were obtained in higher education institutions in Uzbekistan.
Keywords: HEU’, pedagogical strategy, professional education, pedagogical activity